2010
DOI: 10.1007/s10856-010-4184-4
|View full text |Cite
|
Sign up to set email alerts
|

The bioactivity and ion release of titanium-containing glass polyalkenoate cements for medical applications

Abstract: The ion release profiles and bioactivity of a series of Ti containing glass polyalkenoate cements (GPCs). Characterization revealed each material to be amorphous with a T g in the region of 650-660ºC. The network connectivity decreased (1.83-1.35) with the addition of TiO 2 which was also evident with analysis by X-ray Photoelectron Spectroscopy (XPS). Ion release from cements were determined using Atomic Absorption Spectroscopy (AAS) for zinc (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 43 publications
(46 reference statements)
5
14
0
Order By: Relevance
“…They also showed that agitation (sample rotation at 1000 rounds per minute) or aging samples at higher temperature (70°C) significantly increases the ion release of Zn 2+ ions from the cement matrix into the medium, when compared to those aged at 37°C in static conditions. Wren et al [152] investigated titanium (Ti)-containing glasses and found that the immersion of GPCs based on such glasses into distilled water resulted in an increased surface area after 1 day which then decreased over the next 29 days of incubation. The increase in the surface area was attributed to the dissolution of PAA within the cement matrix (hydration processes) resulting in open porosity and thus liberating ions bound within the cement structure, which then sought anionic sites.…”
Section: Ion Releasementioning
confidence: 99%
See 1 more Smart Citation
“…They also showed that agitation (sample rotation at 1000 rounds per minute) or aging samples at higher temperature (70°C) significantly increases the ion release of Zn 2+ ions from the cement matrix into the medium, when compared to those aged at 37°C in static conditions. Wren et al [152] investigated titanium (Ti)-containing glasses and found that the immersion of GPCs based on such glasses into distilled water resulted in an increased surface area after 1 day which then decreased over the next 29 days of incubation. The increase in the surface area was attributed to the dissolution of PAA within the cement matrix (hydration processes) resulting in open porosity and thus liberating ions bound within the cement structure, which then sought anionic sites.…”
Section: Ion Releasementioning
confidence: 99%
“…The release of ions was also influenced by the cross-linked PAA matrix. Studies [152,153] on Ti-containing glasses reported that there was no Ti 4+ release. Shen et al [153] showed that sodium was dissolved at higher rates than calcium and strontium.…”
Section: Ion Releasementioning
confidence: 99%
“…Previous work by the authors has seen the development of a SiO 2 -CaO-SrO-ZnO based GPC series for orthopaedics, in particular for stabilization of osteoporotic vertebral augmentation such as Vertebroplasty and Kyphoplasty [29][30][31][32]. Some properties of these materials, including mechanical and rheological properties and bioactivity were further improved by subsequently substituting titanium (Ti) for the silica content within the glass phase [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive oxygen in octahedral structures requires charge compensation, which may be one possible explanation for the of Ti release from these glasses. 35 Antibacterial testing was conducted for each glass, uncoated and Ag-coated using untreated glass (t ¼ 0) and also glass after 24 h immersion in sterile de-ionized H 2 O (ICP samples, t ¼ 24). Figure 9 presents the antibacterial properties of the uncoated glasses, control, AU-1, and AU-2.…”
Section: Resultsmentioning
confidence: 99%